Revitalizing The Higher Education Curriculum Through An Artificial Intelligence Approach: An Overview - Sanasintani Sanasintani (Yayasan Adra Karima Hubbi, 2023)
Background. Higher education is faced with the challenges of global change which requires innovative curriculum adaptations. In this context, this research aims to develop practical guidelines for higher education institutions in implementing curriculum changes by utilizing artificial intelligence (AI). Purpose. The aim of the research is to develop practical guidelines for higher education institutions in order to implement innovative curriculum changes and responsive to global change. Method. Research methodology uses a quantitative approach with survey design. Identify key variables, including students’ understanding of AI, preferences for AI learning methods, and their views on its impact on the learning experience. The research process involved developing a comprehensive survey instrument with questions designed to gain in-depth insight into student perceptions. The research sample consisted of 20 respondents from higher education program students who were randomly selected. Surveys can be carried out online or through face-to-face interviews. Results. Data analysis involves statistical methods, including descriptive analysis, categorization, and coding to identify patterns in student responses. The survey results reflect a positive level of understanding (70%) and confidence (80%) of students in the role of AI in improving the quality of learning. There is a group that is neutral (20%), indicating the need for further understanding. Conclusion. The survey results create a comprehensive picture of student perceptions and preferences for AI in higher education. Most respondents showed positive acceptance of this technology, with about half expressing a preference for learning involving AI. Overall, this research provides a foundation for higher education institutions to design effective communication and expectation management strategies to ensure optimal acceptance and participation in AI implementation.